Analysis of the Mechanical Behavior of a New Stainless Steel Formwork - Fankui Zeng; Shuxin Yang; Kaiqi Gao; Qi Xiao (Buildings, 2025)
To support national goals of carbon peaking and neutrality, and to promote green, low-carbon development, this study examines the mechanical behavior and deformation characteristics of a novel stainless steel wall formwork under real-world concrete casting conditions. Field experiments were conducted on an active construction site to monitor stress distribution and displacement during concrete placement. A finite element model was established to simulate the mechanical response and validated against field data and theoretical calculations. The results show that the maximum stress and displacement occur mainly in the mid-to-lower regions of the formwork panel. The differences among numerical simulation, theoretical analysis, and field measurements were within 8%, confirming the model’s reliability. Further parametric analysis investigated the effects of varying panel thickness and rib dimensions on mechanical performance. The optimal configuration—panel thickness of 1.25 mm, horizontal ribs measuring 15 mm × 35 mm, and vertical ribs 25 mm × 9 mm—achieved a 10.32% reduction in steel usage compared to the original design, without compromising structural integrity. These findings provide a technical basis for optimizing formwork systems and contribute to resource-efficient and sustainable construction practices.